Hybrids of a 9-anthracenyl moiety and fluorescein as chemodosimeters for the detection of singlet oxygen in live cells - Chercheja, Serghei; Daum, Steffen; Xu, Honggui; Beierlein, Frank; Mokhir, Andriy (Organic & Biomolecular Chemistry, 2019)
Singlet oxygen (1O2) plays an important role in human innate immune response, plant physiology and anticancer photodynamic therapy (PDT). Therefore, its monitoring by convenient and sensitive methods (e.g. by detecting a fluorescence signal) by using non-toxic reagents would be advantageous. Known fluorogenic 1O2-chemodosimeters can potentially consume reducing agents in cells leading to the generation of toxic side products that limit their applications. In this paper we report on a series of 9-anthracenyl-fluorescein hybrids, which do not require any reducing agents for their reaction with 1O2. The selected compound 8d at a very low concentration of 100 nM is able to detect 1O2 in live human promyelocytic leukemia HL-60 cells with over 35-fold fluorescence signal enhancement within only 20 min assay time. This chemodosimeter is not toxic to HL-60 cells at concentrations ≤1 μM (higher concentrations were not tested) even at long incubation times ≤48 h.
CRIS-Team Scopus Importer:2019-12-10